ORGANOLOGI ALAT MUSIK KECAPI DAYAK DI PALANGKA RAYA - Sihombing, Octa Maria; Evalina Awak, Nuryanti (SIWAYANG Journal: Publikasi Ilmiah Bidang Pariwisata, Kebudayaan, dan Antropologi, 2024)
Problems in our research are at the epistemological level of the timbre musicality model, which is often discredited as something inferior compared to the frequency-based model that is generally stigmatized as belonging to the West. The methods of the project are qualitative methods with the technique of visualizing images of Dayak musical instrument making in Central Kalimantan through the work of artists in Palangka Raya. It aims to convey the building materials of the lute, the use of paint, the type of strings and the size of the acoustics of a typical Central Kalimantan lute. Results showed that based on the visualization of the image as a distinguishing space as well as giving the impression that the frequency base on the musicality is not higher than the trimble base on the lute as a stringed instrument. Furthermore, the results show that the making of the Central Kalimantan Dayak harp instrument has a variety of uniqueness in the selection of materials, paint, wood and the characteristics of the harp motif.